Pengaruh Lokasi, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian - Kelvinia Kelvinia; M. Umar Maya Putra; Nasrul Efendi (Jurnal Wira Ekonomi Mikroskil, 2021)
This study aims to determine and analyze the effect of location, price and service quality on consumer purchasing decisions for medical devices at PT. Alexa Medika. The research method used is a qualitative method with a quantitative approach. The study population comes from consumers who have purchased medical devices at PT Alexa Medika. The sample used in this study amounted to 86 people, obtained using a saturated sampling method. Data collection was carried out by distributing questionnaires. The data analysis technique used multiple linear regression analysis with the help of SPSS software. The results showed that location and price partially influenced purchasing decisions and service quality did not partially influence purchasing decisions. Meanwhile, location, price and service quality simultaneously influence purchasing decisions. Furthermore, the result of Adjusted R Square is 31.6%. This shows that the ability of location, price and service quality in explaining purchasing decisions is only 36.1% while 68.4% is explained by other things that are not examined.